Determinan Faktor Risiko Kejadian Stunting Berdasarkan Pemetaan Kasus Stunting pada Balita dengan Geographic Information System (GIS) - Happy Novriyanti Purwadi; Dessy Oktaviani; Kamaluddin Latief (Universitas Faletehan, 2022)
Stunting is an abnormality in the weight and height of babies or toddlers compared to their age. Based on the data from Basic Health Research in 2018 the number of stunting cases in Indonesia was quite high (30.8%). This study aimed to determine the risk factors of stunting based on stunting mapping data with Geographic Information System (GIS) among toddlers. It was a quantitative study and used a case control design. The statistical test used was chi-square and the sampling technique used simple random sampling. The study population was 110 toddlers and the samples were 50 toddlers as cases and 50 toddlers as controls. Legok Health Center work area had a distribution of stunting cases in Rancagong Village as many as 32 points, Serdang Wetan Village 9 points, and Legok Village 9 points. The results showed that exclusive breastfeeding (p=0.543), birth weight (p=0.093), infectious diseases (p=0.141), mother's last education (p=0.830), knowledge of mother's nutrition (p=1.000), feeding style (p=0.541), mother's height (p=1.000), and father's height (p=0.111) were not related to the incidence of stunting. Monitoring of toddlers nutritional status and prevention to the right targets should be maintained and improved to prevent from stunting.